2017
DOI: 10.29063/ajrh2017/v21i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vaginal Lubricants on In-Vitro Progressive Spermatozoa Motility

Abstract: Vaginal lubricants are used to solve intercourse difficulties or as sexual enhancers, but recent reports raise questions about their safety in terms of fertility. In this study, twenty semen samples were tested against commercially available vaginal lubricants for progressive spermatozoa motility and vitality with varying exposure time intervals. Results showed that the vaginal lubricant which least affected progressive spermatozoa motility was the oil-based vaginal lubricant, which kept the mean percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…However, it is notable that AAS users are more likely to take multiple supplements, including protein powders and creatine, other appearance and performance enhancing drugs (APED) and medication for erectile dysfunction(Ip et al 2011) as well as recreational drugs(Kanayama, Pope 2012;. 2.3.1.10 Lubricants Although commonly available, studies have demonstrated most vaginal lubricants to be detrimental to spermatozoa in vitro(Mowat et al 2014;Sandhu, et al 2014;Wilson et al 2017). Their impact on fertility and natural conception is unclear at best(Steiner et al 2012), however the use of vaginal lubricants during intercourse should not be recommended for couples with infertility unless they are able to be deemed 'Sperm safe'Mackenzie & Gellatly 2019).…”
mentioning
confidence: 99%
“…However, it is notable that AAS users are more likely to take multiple supplements, including protein powders and creatine, other appearance and performance enhancing drugs (APED) and medication for erectile dysfunction(Ip et al 2011) as well as recreational drugs(Kanayama, Pope 2012;. 2.3.1.10 Lubricants Although commonly available, studies have demonstrated most vaginal lubricants to be detrimental to spermatozoa in vitro(Mowat et al 2014;Sandhu, et al 2014;Wilson et al 2017). Their impact on fertility and natural conception is unclear at best(Steiner et al 2012), however the use of vaginal lubricants during intercourse should not be recommended for couples with infertility unless they are able to be deemed 'Sperm safe'Mackenzie & Gellatly 2019).…”
mentioning
confidence: 99%